La Documentación en Teletexto - Acebes García, Silvia; Garrido-Lestache Rodríguez, Elena; Gonzalez Sevilla, José; Sánchez Pérez, Carmen (Cuadernos de Documentación Multimedia, 2018)
La Documentación en Teletexto